2017
DOI: 10.1104/pp.17.00118
|View full text |Cite
|
Sign up to set email alerts
|

Scanning for New BRI1 Mutations via TILLING Analysis

Abstract: The identification and characterization of a mutational spectrum for a specific protein can help to elucidate its detailed cellular functions. BRASSINOSTEROID INSENSITIVE1 (BRI1), a multidomain transmembrane receptor-like kinase, is a major receptor of brassinosteroids in Arabidopsis (). Within the last two decades, over 20 different mutant alleles have been identified, which helped to determine the significance of each domain within BRI1. To further understand the molecular mechanisms of BRI1, we tried to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 73 publications
7
30
1
Order By: Relevance
“…In contrast, bri1 cnu1 was much less responsive to exogenous BR and did not reach growth depression with the concentrations tested here (up to 10 nM) (Fig. 2E), as reported for other bri1 hypomorphic alleles of similar strength (Sun et al , 2017). Consistent with the mild growth phenotype, transformation with constructs encoding the two BRI1 mutant versions alone or a combination of both mutations rescued hypomorphic bri1-301 and bri1-null mutants (Fig 3A, B).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…In contrast, bri1 cnu1 was much less responsive to exogenous BR and did not reach growth depression with the concentrations tested here (up to 10 nM) (Fig. 2E), as reported for other bri1 hypomorphic alleles of similar strength (Sun et al , 2017). Consistent with the mild growth phenotype, transformation with constructs encoding the two BRI1 mutant versions alone or a combination of both mutations rescued hypomorphic bri1-301 and bri1-null mutants (Fig 3A, B).…”
Section: Resultssupporting
confidence: 82%
“…These analyses revealed that BR signalling dependent BRI1 functions are only mildly affected in bri1 cnu4 , whereas we observed a strong negative effect on RLP44 function in the regulation of vascular cell fate. Interestingly, the same mutation we report here as bri1 cnu4 , G746A (G2236A on nucleic acid level) has been recently described as bri1-711 in a tilling approach to obtain new bri1 mutants (Sun et al , 2017). Consistent with our results, bri1-711 showed subtle growth defects and mild insensitivity to exogenous application of BL.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Thus, it was proposed that the substitution of Ile-642 (in BRL1) or Met-657 (in BRI1) to Glu-614 (in BRL2) might interfere with the BL binding by changing the hydrophobicity of this region (She et al, 2013). Several bri1 mutants with point mutations in the island domain-LRR interface have been identified (Li and Chory, 1997;Noguchi et al, 1999;Sun et al, 2017). It remains to be demonstrated if BRI1 mutants carrying these molecular lesions are deficient in BR binding, which would further confirm the importance of this region.…”
Section: Bim1 At5g08130mentioning
confidence: 99%
“…Characterization of a mutational spectrum for a specific protein can help to elucidate its detailed cellular functions. To date, over 30 bri1 point mutants with mutant phenotypes have been identified using the approach of genetics, including bri1-5 (Noguchi et al, 1999;Sun C. et al, 2017). In addition, diverse phosphorylation sites in BRI1 were also identified; site-directed mutagenesis followed by in vitro kinase assays of BRI1 kinase domain (KD) and genetic complementation of bri1-5 revealed multiple phosphorylation sites essential for BR signaling in planta (Wang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%